KALIGRAFI SEBAGAI MEDIA EKSPRESI SPIRITUAL TINJAUAN ILMU TASAWUF - Rupa Saluja Zamharira; Liana Pertiwi; Jimi Setiawati (Yayasan Haiah Nusratul Islam, 2025)
Calligraphy is a medium of expression of Sufism that combines aesthetics and spirituality in Islam. This article discusses the history of Sufism calligraphy, an analysis of calligraphy as a medium of Sufism expression, and its implications for Islamic culture. Islamic calligraphy, with its beautiful Arabic writing, has become a powerful medium for expressing spiritual values in Sufism. Through the analysis of various calligraphic works, this study reveals how the shape, color, and composition of letters to be used to convey mystical messages and inspire Muslims. Sufism is a nameless form of worship that produces knowledge that aims to perfect human morals and make them more obedient to Allah SWT. In the science of Sufism, there are many schools of Sufism, one of which is irfani Sufism, which is an approach taken by creatures through an inner approach or what is often called ma`rifat science.